The Effect Of K3 On Employee Productivity Through Company Commitment And Culture: Systematic Literature Review (SLR) With Bibliometrics - Farika Nursasi; Budi Eko Soetjipto; Madziatul Churiyah (PT. Maju Malaqbi Makkarana, 2026)
This study aims to systematically analyze the influence of Occupational Safety and Health (K3) on employee productivity through organizational commitment and company culture using the Systematic Literature Review (SLR) approach. K3 has a strategic role in creating a safe and healthy work environment, which not only contributes to reducing the number of occupational accidents and occupational diseases, but also has implications for improving employee performance and productivity. However, the relationship between K3 and productivity is not always direct, but rather influenced by psychological and organizational factors, especially organizational commitment and company culture. This study uses the SLR method with PRISMA steps. Articles filtered from the Scopus journal database with the topic The study process is carried out systematically through the stages of identification, screening, feasibility assessment, and determination of final articles in accordance with the inclusion and exclusion criteria that have been set. The results of the study show that the effective implementation of K3 has a positive effect on employee productivity both directly and indirectly. Organizational commitment acts as a mediator that strengthens these relationships through increased employee loyalty, attachment, and responsibility, while a company culture that supports safety values strengthens collective norms and performance orientation in Indonesia published between 2021 and 2026 in a total of 5,863 articles. After elimination according to the criteria, only 41 articles were considered and extracted. These findings confirm that K3 is not only seen as a regulatory obligation, but as a strategic instrument in human resource management to improve the sustainability and competitiveness of the organization. Theoretically, this study integrates the concepts of K3, organizational commitment, company culture, and productivity in a comprehensive conceptual framework, and practically provides managerial implications in strengthening performance based on work safety.